Attributes and Characteristics that Stimulate Innovation Leader's Creativity - Mishra, Ganesh Prasad; Mishra, Lata Kusum (International Journal of Management Excellence (ISSN: 2292-1648), 2017)
Today organizations face a scarcity of innovation leaders. Innovation leaders are successful because of the attributes and characteristics they possess. Characteristics and attributes of three innovation leaders -Thomas A. Edison, Steve Jobs and Mark Zuckerberg has been highlighted in this project. These innovation leaders are termed as highly creative and innovative. The author conducted a review of many international publications related to innovation leader. Some of the attributes of an innovation leader that were found in the research are - possessing strong leadership, must be visionary, must act as change agent so that employees are able to change their process and system for the betterment, must be a good sales person to sell ideas to the people, must be a good listener to understand others requirements, must be a logical thinker to make decisions, must be a good team-builder, must be even-keeled demeanour to act in an unbiased manner, must be passionate about new ideas and concept, and must be optimistic. It has also been found and widely acknowledged that innovation leaders play a critical role in organization's success.